Investigation of potential numerical acoustic treatment for SMK Ayer Keroh hall - M.Z., Nurul Nadiah; H., Mohd Nor; M.I., Imran; M., Jantul Islah (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June, 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.